An analysis report to reduce the employee attrition within organizations. (17th February 2020) - Srivastava, Devesh Kumar; Tiwari, Pradeep Kumar
Abstract: The analysis has been carried to find out the most critical factor that affects an employee's attrition. The opposite of attrition is retention. As employee's attrition very negatively affect companies' growth, every year companies come with different retention schemes for employee, so employees don't leave the company. Those methods include retention bonuses, better training, promotion and stock option which mature after some definite period. So finding the essential factor for attrition will help organization to plan their retention schemes more targeted.